Reverse complement-PCR, an innovative and effective method for multiplexing forensically relevant single nucleotide polymorphism marker systems - Bus, Magdalena M (BioTechniques, 2021)
DNA analyses from challenging samples such as touch evidence, hairs and skeletal remains push the limits of the current forensic DNA typing technologies. Reverse complement PCR (RC-PCR) is a novel, single-step PCR target enrichment method adapted to amplify degraded DNA. The sample preparation process involves a limited number of steps, decreasing the labor required for library preparation and reducing the possibility of contamination due to less sample manipulation. These features of the RC-PCR make the technology a unique application to successfully target single nucleotide polymorphisms (SNPs) in fragmented and low copy number DNA and yield results from samples in which no or limited data are obtained with standard DNA typing methods. The developed RC-PCR short amplicon 85 SNP-plex panel is a substantial improvement over the previously reported 27-plex RC-PCR multiplex that will provide higher discrimination power for challenging DNA sample analyses